ANALISIS KINERJA PMS REL 2 BAY TRAFO 6 MENGGUNAKAN THERMOVISION METHODE DI GARDU INDUK SUNYARAGI - Agus Siswanto; Reza Alfian; Erfan Subyanta (Foristek, 2021)
In an effort to provide reliable and efficient electrical energy, substations have an important role in regulating the demand for electric power loads and as a center for securing electrical power system components in a certain area. Frequent disturbances become a benchmark for an electric power system whether or not it is good or not in an effort to provide reliable and efficient energy. One of the maintenance measures is temperature measurement using thermal imagers, which is commonly referred to as thermovision measurement.Thermal imager is a tool that can be used for predictive maintenance activities to monitor the condition and performance of an equipment so that the possibility of equipment failure can be minimized. In October 2020, after thermovisiting transformer bay 6 at the Sunyaragi substation, it was discovered that there was a hotspot on the T-phase separation blade, causing heating of the blade, the above conditions can result in a decrease in PMS performance, with the worst condition if left alone can result in damage to the PMS blade and can also melt when the peak load is on the transformer 6. Under these conditions, maintenance is carried out by maintaining contact resistance, insulation resistance, and grounding resistance. The results of the analysis of contact resistance after maintenance show that the equipment is in good condition and still suitable for use, with a value of 7μΩ for the R phase, 6.5μΩ for the S phase, and 6.7μΩ for the T phase.